Experimental and mechanistic investigation of the residual stress in SiCP/Al composites at the multi scale - Jiaqi Li; Weiguang Zhang; Xueping Zhao; Fengchao Lang; Yongming Xing (Materials & Design)
Silicon carbide particle-reinforced aluminum matrix composites (SiCP/Al) represent a novel structural material. The performance differences between the SiC particles and the Al matrix result in a non-uniform distribution of residual stresses within the composite, which significantly affecting its mechanical properties. This study characterizes the residual stress distribution patterns within the SiC particles at the micron-scale using micro-Raman spectroscopy and transmission electron microscopy (TEM). It also analyzes the fracture behavior of these particles, considering the influence of residual stresses, through a combination of geometric phase analysis (GPA) and the Yoffe model. The interior of SiC particle experiences residual tensile stress, whereas the interface region is under compressive stress. Additionally, irregular SiC particle shapes contribute to fluctuations in residual stress. The fracture behavior is primarily influenced by a combination of factors, including residual stresses arising from thermal mismatch and externally induced loads. TEM observations confirm the presence of Mg-Si IMC at the interface of the composite material. These compounds form a coherent interface with both the Al matrix and SiC phase enhancing interfacial properties. A high dislocation density in the microstrain regions adjacent to the coherent interface is identified as the main contributor to residual stress at the interface of composite material.